Cochlear Implants in Children Diagnosed with CHARGE Syndrome - Cardoso,Carolina Costa (2013)
Introduction  The CHARGE association (coloboma of the eyes; heart disease; atresia of the choanae; retarded growth and development; genital hypoplasia/genitourinary anomalies; ear anomalies and/or hearing loss) was first described in 1979 by Hall, and among its main features is hearing loss. This study presents a case aiming to establish relationships between performance on Infant Toddler Meaningful Auditory Integration Scale (IT-MAIS) and Meaningful Use of Speech Scales (MUSS) tests and the analysis of hearing and language categories of a patient diagnosed with CHARGE syndrome, before and after cochlear implant (CI) surgery. Case Report  A 7-year-old girl was diagnosed with CHARGE. She had severe sensorineural hearing loss and was a prelingual unilateral CI user. We analyzed data from the patient's medical records regarding therapies and video recordings. Results  The patient showed positive results in all evaluations after CI. IT-MAIS rose from 5 to 90% following the use of CI. MUSS also rose, from 75 to 72.5%, after use of CI. Classification of Auditory Skills changed from category 1 before use of CI to category 6 after use of CI. Classification of Language Skills changed from category 1 before use of CI to category 3 after use of CI. The CI is an aid but there are many factors in the therapeutic process, and great heterogeneity in individuals diagnosed with CHARGE should be investigated. Conclusion  The development of listening and language skills after CI use was demonstrated by IT-MAIS and MUSS tests, and categorization of speech and hearing in this child with a diagnosis of CHARGE syndrome shows that CI can be an effective technological resource to provide information on hearing as one source for language construction.